PENGARUH PENYULUHAN TERHADAP PENGETAHUAN DAN SIKAP IBU PKK TENTANG PEMERIKSAAN PAYUDARA SENDIRI (SADARI) - Huda Nuri Suraya; Ilhami Romus; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2015)
ABSTRACTBackground: Counseling is one of the approaches attempt to improve the knowledge and attitudes. This study aimed to determine the effect of counseling on knowledge and attitudes Family Welfare Movement about breast self examination (BSE) at Tangkerang Timur District of Pekanbaru. BSE is one of the method for early detection of breast cancer. Materials and Methods: A analitic one group pretest-postest that using questionnaire was conducted amongst 36 person Family Welfare Movement at Tangkerang Timur District, Pekanbaru. Measurement data of knowledge and attitudes took 2 times, before and after counseling. The counseling perform using presentation method and pantom simulation. Results: The result of knowledge and attitudes about BSE before and after counseling is that the knowledge level before counseling on the respondent in high category is about 22 (61,1%) respondent and low category is about 14 (38,9%) respondent. After the counseling, there was incerasing number of respondent whom in high category to be 26 (72,2%) respondents and decreasing number of respondent in low category to be 10 (27,8%) respondent. The attitude level before counseling in categorized positive which 19 (52.8%) of respondents and negative categories is 17 (47.2%) of respondents. After counseling an increase of respondents are positive that 22 (61.1%) of respondents and decrease the negative attitude of the respondents is 14 (38.9%). The changes in knowledge and attitudes group Family Welfare Movement about knowing before and after counseling by using Mc.Nemar test obtained Significancy figures show the number 0.388 to 0.549 for the knowledge and attitudes. The p-value of 0.05, the results indicate a change in knowledge and attitudes about BSE before and after counseling, but not significant. Multivariate analysis was discontinued because the bivariate analysis has a value of p> 0.25. Conclusion: The counseling influence on improving knowledge and attitudes Family Welfare Movement RW IX Tangkerang Timur District.Keywords: knowledge, Attitude, counseling, breast self examination